Angry management : three novellas - Crutcher, Chris (Greenwillow Books, 2009)
Every kid in this group wants to fly. Every kid in this group has too much ballast. Mr. Nak's Angry Management group is a place for misfits. A place for stories. And, man, does this crew have stories. There's Angus Bethune and Sarah Byrnes, who can hide from everyone but each other. Together, they will embark on a road trip full of haunting endings and glimmering beginnings. And Montana West, who doesn't step down from a challenge. Not even when the challenge comes from her adoptive dad, who's leading the school board to censor the article she wrote for the school paper. And straightlaced Matt Miller, who had never been friends with outspoken genius Marcus James. Until one tragic week<U+2014>a week they'd do anything to change<U+2014>brings them closer than Matt could have ever imagined.